Nanotechnology : ethical and social implications - Khan, Ahmed S. (Nano and energy series, 2012)
"Preface Historically, every new technological advance and innovation remakes the world. The time to remake the world has become shorter with every new technological revolution. The Industrial Revolution took almost two centuries to reshape the world, the electronics revolution around 70 years, the information revolution two decades, and innovations in biotechnology and nanotechnology to reshape the world could be just a matter of less than a decade. The projected impact of nanotechnology has been touted as a second industrial revolution--not the third, fourth, or fifth, because despite similar predictions for technologies such as computers and robotics, nothing has yet eclipsed the first. Society is at the threshold of a revolution that will transform the ways in which materials and products are created. How will this revolution develop? The opportunities that will develop in the future will depend significantly upon the ways in which a number of challenges are met. As we design systems on a nanoscale, we develop the capability to redesign the structure of all materials--natural and synthetic--along with rethinking the new possibilities of the reconstruction of any and all materials. Such a change in our design power presents tremendous social and ethical questions. To enable our future leadership to make decisions for sustainable ethical, economic nanotechnological development, it is imperative that we educate all nanotechnology stakeholders about the short-term and long-term benefits, limitations, and risks of nanotechnology. The social implications of nanotechnology encompass many fundamental areas such as ethics, privacy, environment, and security"--